Description of the Implementation of Pneumonia Diagnosis Coding Based on Education, Knowledge and Work Period of the Coder (Dr. M. Yunus Hospital Bengkulu) - Budiarti, Anggia; Harmanto, Deno; Ayu, Dinda (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2023)
Coders are fully responsible for the accuracy of diagnosis coding, therefore officers must have good knowledge and high experience so that coding activities can be carried out well, based on a survey conducted by researchers at RSUD Dr. M. Yunus Bengkulu, pneumonia ranks 3rd out of the 10 most common illnesses in inpatients at RSUD Dr. M. Yunus Bengkulu, by checking the entry and exit sheets in the medical record files for those diagnosed with pneumonia, there were 11 diagnoses whose diagnosis codes were incorrect, which would hamper the claim process and would affect the quality of medical record services. The purpose of this research is to determine the knowledge and work experience of coders in carrying out codefication of pneumonia diagnoses at RSUD Dr. M. Yunus Bengkulu. The type of research carried out is descriptive research, namely describing the results of the data obtained. The research objects were 65 medical record files for pneumonia diagnosis and the research subjects were 5 coders. The method used is observation using a check list sheet and questionnaire sheet. Data collection uses secondary and primary data. Of the 65 medical record files for pneumonia diagnosis, 54 or (70%) had correct codes and 11 or (30%) had incorrect codes. 5 people or (100%) coders have worked for ≥3 years. 2 respondents or (40%) had good knowledge, and 3 people or (60%) officers had sufficient knowledge.